The Future of Gas - Bassam Fattouh; Jonathan Stern (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2018)
This issue of the Oxford Energy Forum looks at the future of gas from different perspectives. Future development of decarbonised gases – biogas, biomethane and hydrogen – and the consequences for gas networks. The importance of reducing methane emissions from the gas chain. Progress towards reducing the costs of liquefaction and the affordability of gas and LNG imports, particularly in low income countries. The potential for gas to penetrate new markets and specifically the marine transport sector. And the enduring issue of security of supply as a potential constraint on the future of the fuel.
Keywords: 330